Antioxidant properties of novel dimers derived from natural β‑elemene through inhibiting H2O2‑induced apoptosis - Chen, Jichao; Wang, Ruifan; Wang, Tianyu; Ding, Qilong; Khalil, Aliahmad; Xu, Shengtao; Lin, Aijun; Yao, Hequan; Xie, Weijia; Zhu, Zheying; Xu, Jinyi (American Chemical Society, 2017)
A series of novel β-elemene dimer derivatives were synthesized and evaluated for their antioxidant activities. The results indicated that most of the target compounds showed more potent cytoprotective effects than positive control vitamin E. In particular, dimer D5 exhibited the strongest antioxidant activity, which was significantly superior to the active compound D1 obtained in our previous study. Besides, D5 did not produce obvious cytotoxicity in normal human umbilical vein endothelial cells (HUVECs) and increased the viability of HUVECs injured by H2O2 in a concentration-dependent manner. Further studies suggested that the cytoprotective action of D5 might be mediated, at least in part, by increasing the intracellular superoxide dismutase activity and nitric oxide secretion as well as decreasing the intracellular malonyldialdehyde content and lactate dehydrogenase release. Furthermore, D5 observably inhibited ROS generation and prevented H2O2-induced apoptosis in HUVECs possibly via inhibiting the activation of the MAPK signaling pathway.